Classic Mataraman Folktales for Improving Qira’ah among Arabic Language and Literature Students: A Local Cultural Approach - Dewi, Intan Sari; Ridwan, Muhammad Mahfud Ridwan; Muhammad Faishol Al Hamimy; Filefil, Ahmed Abdul Hadi Abdul Jawwad (Arabiyatuna: Jurnal Bahasa Arab, 2025)
In qira’ah instruction, standardized Arabic texts often fail to engage students from culturally rich regions. This study examines how integrating classic Mataraman folktales can enhance qira’ah outcomes while strengthening cultural identity among Arabic Language and Literature students. The research responds to the need for culturally responsive pedagogy that bridges foreign language acquisition with the preservation of local culture in Indonesian Islamic higher education, where Arabic language mastery often feels detached from students’ lived experiences. Using a qualitative case study approach at UIN Sayyid Ali Rahmatullah, Tulungagung, data were collected through participatory observation across 12 sessions, semi-structured interviews with 26 students and three lecturers, and analysis of instructional materials. Triangulation and member-checking techniques ensured data validity. Findings revealed that incorporating Mataraman folktales, specifically the tales of Gunung Budeg, Lembu Peteng, and Putri Gayatri, increased student motivation by 78%, text comprehension by 65%, and cultural identity by 83%. Qira’ah skills improved significantly across literal comprehension (18%), inferential comprehension (23%), critical comprehension (23%), and reading–writing integration (17%), with statistical significance (p < 0.05). Thematic analysis further revealed greater emotional engagement, improved vocabulary retention, and a strengthened sense of learner identity. This study provides empirical support for culturally sustaining pedagogical practices and proposes a practical framework for integrating indigenous cultural resources into foreign language education.